Effect of Hot-pressing Conditions on the Physicochemical Properties and Flavor of Gelatin Extracted from Sturgeon Cartilage (SCG) - Zefan CHEN; Xiangzhi LU; Jinlin WANG; Fan BAI; Peng XU; Yuanhui ZHAO (Shipin gongye ke-ji, 2025)
In order to explore the effects of different hot-pressing conditions on the physicochemical properties and flavor quality enhancement of gelatin extracted from sturgeon cartilage (SCG) and expand its potential applications, sturgeon cartilage was used as raw material for the production of SCG via hot-pressing extraction at 115 ℃ (0.07 MPa) and 121 ℃ (0.12 MPa) for 20, 30, 40, and 50 min. Colorimetry, Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectrophotometry (UV-vis), sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and scanning electron microscopy (SEM) were used to determine the physicochemical properties of SCG. The flavor differences in SCG samples were analyzed by sensory evaluation, gas chromatography-ion mobility spectrometry (GC-IMS), and gas chromatography-mass spectrometry (GC-MS). In terms of physicochemical properties, with the elevation of hot-pressing temperature and extension of time, SCG exhibited deepened coloration and enhanced degradation effects. Specifically, the L* value of SCG significantly decreased from 63.15±1.49 to 55.91±0.35 (P<0.05), while both a* and b* values significantly increased (P<0.05). With molecular weights focusing on peptides<25 kDa, SDS-PAGE bands significantly faded. The absorption peak of the amide I band moved towards shorter wavenumbers, and the proportion of α-helix structures completely changed to random coils, β-sheets and β-turns. A finer and more distributed fragmented morphology was observed microscopically. These alterations manifested the pivotal role of hot-pressing treatment in facilitating the structural degradation of SCG. The analysis of flavor indicated that under more intense hot-pressing conditions, the total free amino acid content of SCG increased from 0.35±0.04 mg/g to 0.85±0.06 mg/g with umami amino acids (aspartic acid and glutamic acid) increasing from 22.02% to 39.43% while bitter amino acids (leucine) decreased from 74.60% to 57.79%. There was a decrease in off-flavors and an increase in specific flavor compounds such as methyl propionate, 2-butanone, and citronellal transmitting fatty, roasted, and fruity aromas. Collectively, these changes significantly improved the flavor quality of SCG. In addition, with the highest sensory scores for fatty aroma (7.87±0.76), umami taste (4.34±0.36), and roasted aroma (8.21±0.87), SCG made at 121 ℃ for 50 min showed the best flavor quality. In conclusion, moderate increases in hot-pressing temperatures and duration resulted in greater degradation effects on SCG and positively contributed to its flavor quality improvement.